2014
DOI: 10.1002/adma.201306323
|View full text |Cite
|
Sign up to set email alerts
|

Strong Photocurrent Enhancements in Highly Efficient Flexible Organic Solar Cells by Adopting a Microcavity Configuration

Abstract: Organic solar cells often show inefficient light harvesting due to a short absorption path length limited by the low charge mobility of organic semiconductors. We demonstrate a flexible organic solar cell in a microcavity configuration using a TeO2/Ag semitransparent electrode to confine the optical field within the device with significant performance improvements and reaching a power conversion efficiency of 8.56%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 49 publications
1
73
0
Order By: Relevance
“…The state‐of‐the‐art single‐junction OSCs with plasmonic cavity structures,1, 2, 3 textured light trapping structures,4, 5 multiplasmonic effects,6, 7, 8 morphological implementation,9, 10 bandgap tuning,11, 12 and solution fabrication method13 now provide over 8–11% of power conversion efficiency (PCE) based on the above approaches or a combination of these approaches. However, over the past few years, a serious difficulty has also been observed in the increase of the PCE of single‐junction OSCs to over 12%.…”
Section: Introductionmentioning
confidence: 99%
“…The state‐of‐the‐art single‐junction OSCs with plasmonic cavity structures,1, 2, 3 textured light trapping structures,4, 5 multiplasmonic effects,6, 7, 8 morphological implementation,9, 10 bandgap tuning,11, 12 and solution fabrication method13 now provide over 8–11% of power conversion efficiency (PCE) based on the above approaches or a combination of these approaches. However, over the past few years, a serious difficulty has also been observed in the increase of the PCE of single‐junction OSCs to over 12%.…”
Section: Introductionmentioning
confidence: 99%
“…This electrode must be deposited when the absorber layer has already been deposited on the substrate and a nonaggressive deposition procedure needs to be used. Several different options have been considered, such as low-temperature annealed indium tin oxide (ITO), [42][43][44][45][46][47][48] a three-layer architecture combining a dielectric layer, an ultra thin metal layer, and a second dielectric layer, [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] PEDOT, [65][66][67] silver grid, 68 graphene, [69][70][71] carbon nanotubes, 67,72 and silver nanowires (AgNW). [73][74][75][76][77][78] However, the need for a nondestructive deposition technique for the top semi-transparent electrode is probably not the major issue that semi-transparent OPV cells must overcome before becoming an industrially viable solution.…”
Section: Introductionmentioning
confidence: 99%
“…Incident light with resonant frequencies can be trapped inside the metal microcavity, satisfying the constructive interference condition, which realizes the effective light trapping in the sandwiched active layer [152][153][154]. Ultrathin metal films are usually chosen as the semitransparent front electrode with superior reflective transparent characteristics compared with the commonly used transparent ITO electrode, which ensures the formation of a stronger microcavity to enhance the optical confinement in OPVs.…”
Section: Metal-mirror Resonant Microcavitymentioning
confidence: 99%
“…Jen et al [152,161,162] have demonstrated ITO-free OPVs with the microcavity structure based on an ultrathin Ag electrode. The transmitted incident light through the ultrathin Ag electrode resonated within the optical microcavity, and photons with resonant frequencies were trapped owing to the coherent interference.…”
Section: Metal-mirror Resonant Microcavitymentioning
confidence: 99%